Effect of Supplementation with Green and Black Tea on Microbiological Characteristics, Antimicrobial and Antioxidant Activities of Drinking Yoghurt - Gülfem Ünal; Cem Karagözlü; Özer Kınık; Ayşe Sibel Akalın; Ecem Akan (Journal of Agricultural Sciences)
The influence of supplementation with green and black tea on microbiological properties, antimicrobial and antioxidant activities of drinking yoghurt were investigated during 21 days of storage. The samples supplemented with 2% either green or black tea had higher viable counts of both yoghurt starter bacteria than those of infused by the ratio of 4%. Both green and black tea extracts showed antimicrobial activity on E. coli, B. cereus, S. aureus and C. albicans however this effect was detected higher in samples containing green tea. The samples added green tea extract had the highest DPPH scavenging activity when compared to those supplemented with black tea extract throughout the storage. Green tea had a superior effect than black tea in terms of total phenolic content of drinking yoghurt samples.